Long-term immunologic and virologic responses on raltegravir-containing regimens among ART-experienced participants in the HIV Outpatient Study. Issue 4 (August 2015) - Buchacz, Kate; Wiegand, Ryan; Armon, Carl; Chmiel, Joan S.; Wood, Kathleen; Brooks, John T.; Palella Jr., Frank J.
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: Raltegravir (RAL)-containing antiretroviral therapy (ART) produced better immunologic and virologic responses than optimized background ART in clinical trials of heavily ART-experienced patients, but few data exist on long-term outcomes in routine HIV care. Methods: We studied ART-experienced HIV outpatient study (HOPS) participants seen at 10 US HIV-specialty clinics during 2007–2011.We identified patients who started (baseline date) either continuous ≥ 30 days of RAL-containing or RAL-sparing ART, and used propensity score (PS) matching methods to account for baseline clinical and demographic differences. We used Kaplan–Meier methods and log-rank tests for the matched subsets to evaluate probability of death, achieving HIV RNA < 50 copies/ml, and CD4 cell count (CD4) increase of ≥ 50 cells mm− 3 during follow-up. Results: Among 784 RAL-exposed and 1062 RAL-unexposed patients, 472 from each group were matched by PS. At baseline, the 472 RAL-exposed patients (mean nadir CD4, 205 cells mm− 3; mean baseline CD4, 460 cells mm− 3; HIV RNA < 50 copies ml− 1 in 61%; mean years on prescribed ART, 7.5) were similar to RAL unexposed. During a mean follow-up of over 3 years, mortality rates and immunologic and virologic trajectories did not differ between the two groups. Among patients with detectable baseline HIV RNA levels, 76% of RAL-exposed and 63% of RAL-unexposed achieved HIV RNA < 50 copies ml− 1 (P = 0.51); 69 and 58%, respectively, achieved a CD4 increase ≥ 50 cells mm− 3 (P = 0.70). Discussion: In our large cohort of US ART-experienced patients with a wide spectrum of clinical history, similar outcomes were observed when prescribed RAL containing versus other contemporary ART.